Molecular Identification Of Fish Larvae In Merbok River Through Dna Metabarcoding - Alshari, Norli Fauzani Mohd Abu Hassan (2020)
This study aimed to elucidate the diversity and distribution of fish larvae in Merbok River through molecular identification by the DNA metabarcoding approach. In the first phase of this study, a molecular database for the fish species of Merbok River was completed through the expansion of the existing reference database of 12S ribosomal RNA (rRNA) gene for the 120 documented species morphologically identified in previous studies in combination with existing Cytochrome Oxidase Subunit 1 (COI) database. In the second phase, a metabarcoding study of fish larvae samples obtained from four stations (St1, St2, St3 and St4), representing the upper to lower zone of a lower to higher salinity gradient was conducted. The genomic DNA of the fish larvae were extracted, amplified and enriched by using REPLI-g Mitochondrial DNA kit. Next generation sequencing (NGS) of this whole genome was done using the Illumina MiSeq platform, followed by bioinformatics analysis. A BLAST analysis on the de novo assembled scaffolds of the four samples detected a total of 89 fish larvae species, 65 genera and 41 families from 1071 and 943 total genome scaffolds belonging to COI and 12S rRNA genes, respectively. From the total number of scaffolds, Oryzias javanicus and Oryzias dancena showed the highest abundance and followed by other estuarine species commonly found such as Lutjanus argentimaculatus, Lutjanus malabaricus and others. Considerable non-overlapping of species identity between the metabarcoding and morphological data is suggested to be due to variation in spawning season and sampling biasness (commercial compared to wild species) among other factors.